(untitled) (Current Horticulture, 2024)
An experiment was conducted to find out the effect of nitrogen in growth, yield, seed and economics of French bean (Phaseolus vulgaris L.) at Bahadari farm, College of Horticulture, Mandsaur, Madhya Pradesh, during rabi season of 2009-10. Fifteen treatment combinations comprising three varieties, viz. V1, Swaran Priya; V2, Arka Komal and V3, Contender and five nitrogen levels, viz. N1, 25 kg/ha N; N2, 50 kg/ha N; N3, 75 kg/ha N; N4, 100 kg/ha N and N5, 125 kg/ha N were tested in factorial randomized block design with three replications. The varieties differed significantly for growth, yield and quality parameters, and yield. Maximum plant height, leaf area index and dry weight of shoots/plant were recorden in Swaran Priya. Earliest 50 per cent flowering was commenced in Contender, followed by Swaran Priya with no remarkable difference. Maximum length of pod, seeds/pod, seed yield/plant, seed yield/ha, shelling percentage, test weight as well as germination percentage were recorded with Swaran Priya. Crude protein content in seed was highest in Arka Komal. Application of nitrogen levels indicated significant effect on growth, yield and seed quality. Maximum plant height, leaf area index and dry weight of shoots/plant were observed with application of N4 (100 kg/ha N). Earliest 50 per cent flowering was observed under N1 (25 kg/ha N) application. Maximum pod length (cm), seed yield (g)/plant, seed yield (q)/ha and shelling percentage were recorded with N4 (100 kg/ha N). Maximum seeds/pod, test weight, crude protein content in seed and germination percentage were determined with application of N5 (125 kg/ha N). Highest gross return, net return as well as net return per rupees investment were realized with Swaran Priya under N4 (100 kg/ha N) application.